Vermi-composting fetches good returns - Singh, B P; Tomar, Manish; Pandey, Rakesh; Singh, Deepa (Indian Farming, 2018)
Mr P. Bajaj further stated that many times the foreign ingredients in dung hamper the proper conversion process of dung into compost. Gaining experiencing on the basis of learning by doing and on the advisories of KVK’s SMS, he keeps improving his vermicompost unit. Now he is producing the fine quality of vermicompost which has high demands among the farmers specifically among the vegetable farmers and in plant nurseries in Bareilly district. He is receiving supply order not only from the district of Uttar Pradesh but also from Uttrakhand.